Efektivitas Pembelajaran Number Heads Together Terhadap Berpikir Kritis Siswa Kelas IV Pembelajaran PPKn - Fatimah, Siti (Prodi Pendidikan Guru Sekolah Dasar, 2024)
The general learning objectives as well as the members of the study group's social, physical, and mental characteristics are all part of the effectiveness of learning. Students' critical thinking abilities may be improved by learning number heads collectively. The capacity for critical thinking entails the capacity for reasoned, reasonable thought as well as the capacity for problem-solving. Students can develop their personalities and be able to articulate their ideas by using critical thinking. The type of research that was employed was descriptive quantitative research, and the purpose of this study was to describe and describe in a factual, methodical, and precise manner the usefulness of using number heads alongside learning to foster critical thinking in elementary school kids. It is well known that the t-count, which is 6,007 > 2,093, exceeds the t-table. with a 2-tailed sig. value of 0.000. H1 is accepted and H0 is denied because it can be observed that the significant value of 0.000 is less significant than the significance of 0.05 (0.000 0.05). This indicates that there is a considerable difference in the effectiveness of teaching pupils to think critically before and after using number heads together.